Analysis of Picky Eater Behavior in Mustika Siwi Kindergarten Students in Terms of Eating Patterns at Home - Syifah, Khalwah Khuknatus; Zulfahmi, Muhammad Nofan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Picky eater behavior, or children who have difficulty eating, can be a confusing and worrying challenge for parents and teachers alike. In Mustika Siwi Kindergarten, this phenomenon is a serious concern because it can have an impact on children's health and development. This problem not only affects the nutritional aspect of the child, but can also cause anxiety, stress, and conflict among parents, teachers, and children. The purpose of this study was to explore and analyze picky eater behavior in Mustika Siwi Kindergarten (TK) students, focusing on eating patterns at home. This research method uses the method used in this writing in the form of qualitative methods using a descriptive analysis approach. The results of this study show that in tracing picky eater behavior in Mustika Siwi Kindergarten students, it can be concluded that eating patterns at home have a significant impact on children's tendency to choose food types. The results of the analysis revealed that limited food variations, special rules related to food, and interactions during meals at home play a key role in the emergence of picky eater behavior. Steps to address this problem not only include parental education, but also involve close collaboration between parents and teachers. Strategies of a positive approach to food, increasing menu variety in schools, and creating a pleasant eating experience at home are important elements in creating positive change.